Assessment of left ventricle magnetic resonance temperature stability in patients in the presence of arrhythmias. (9th August 2019) - Ozenne, Valéry; Bour, Pierre; de Senneville, Baudouin Denis; Toupin, Solenn; Vaussy, Alexis; Lepetit‐Coiffé, Matthieu; Jaïs, Pierre; Cochet, Hubert; Quesson, Bruno
Abstract: Background: Magnetic resonance (MR) thermometry allows visualization of lesion formation in real‐time during cardiac radiofrequency (RF) ablation. The present study was performed to evaluate the precision of MR thermometry without RF heating in patients exhibiting cardiac arrhythmia in a clinical setting. The evaluation relied on quantification of changes in temperature measurements caused by noise and physiological motion. Methods: Fourteen patients referred for cardiovascular magnetic resonance imaging underwent an extra sequence to test the temperature mapping stability during free‐breathing acquisition. Phase images were acquired using a multi‐slice, cardiac‐triggered, single‐shot echo planar imaging sequence. Temperature maps were calculated and displayed in real‐time while the electrocardiogram (ECG) was recorded. The precision of temperature measurement was assessed by measuring the temporal standard deviation and temporal mean of consecutive temperature maps over a period of three minutes. The cardiac cycle was analyzed from ECG recordings to quantify the impact of arrhythmia events on the precision of temperature measurement. Finally, two retrospective strategies were tested to remove acquisition dynamics related either to arrhythmia events or sudden breathing motion. Results: ECG synchronization allowed categorization of inter‐beat intervals (RR) into distinct beat morphologies. Five patients were in stable sinus rhythm, while nine patients showed irregular RR intervals due to ectopic beats. An average temporal standard deviation of temperature of 1.6°C was observed in patients under sinus rhythm with a frame rate corresponding to the heart rate of the patient. The temporal standard deviation rose to 2.5°C in patients with arrhythmia. The retrospective rejection strategies increased the temperature precision measurement while maintaining a sufficient frame rate. Conclusions: Our results indicated that real‐time cardiac MR thermometry shows good precision in patients under clinical conditions, even in the presence of arrhythmia. By providing real‐time visualization of temperature distribution within the myocardium during RF delivery, MR thermometry could prevent insufficient or excessive heating and thus improve safety and efficacy. Abstract : The present study was performed to evaluate the precision of MR thermometry without radiofrequency heating in 14 patients exhibiting cardiac arrhythmia. The evaluation relied on quantification of changes in temperature measurements caused by noise and physiological motion. A temporal standard deviation around 2°C was observed, indicating that real‐time cardiac MR thermometry shows good precision in patients, even in the presence of arrhythmia.